Attitudes toward the Aged of Persons Under and Over the Age of Forty - Signori, Edro I.; Butt, Dorcas Susan; Kozak, John F. (Canadian Journal of Counselling and Psychotherapy, 2012)
An analysis of attitudes to'ward persons '65 years or older' yielded five factors: Integrity, Fortitude, Social Appeal, Dependability, and Open-mindedness. When the 716 respondents were divided into those aged 40 and over and those under 40, ratings by the older respondents yielded two additional factors: Competence and Reflectiveness. Analyses by sex showed Integrity accounting for the greatest variance in the ratings by females while Social Appeal accounted for the greatest variance in the ratings by males. An unfavourable stereotype of the older person was manifested in the negative pole of Open-mindedness (Rigidity). Positive attitudes toward the elderly were manifested in the variables comprising the first four factors, but this positive stereotype is rarely reported in the literature.